IoT-Enabled Intelligent Surveillance Robot for Multi-Application Security and Monitoring - Kusuma Devi. G.H; Grandhe Gowtham; Abhishek Aili; Bhargav S; Harshith M; Prajwal V M (Innovative Solutions: A Systematic Approach Towards Sustainable Future, Edition 1, 2025)
Aims: The aim of this project is to design and develop an IoT-based Smart Multi- Application Surveillance Robot to reduce casualties on the battlefield by enhancing security and monitoring capabilities. The robot is intended to capture intruder information, neutralize threats, and perform multiple applications such as bomb detection in public places. Study Design: Controlling the robot in manual mode using IoT technology via Android/PC. Implementing a wireless vision camera for live video streaming. Integrating PIR (Passive Infrared) and metal detection sensors. Utilizing location tracking technology. Methodology: IoT Control: The robot’s movement is controlled remotely using an Android phone or PC, overcoming short-range communication issues. Surveillance and Detection: The robot uses a wireless vision camera for live video streaming, and PIR and metal detectors for identifying intruders and potential threats. Threat Neutralization: Upon detecting an intruder or metallic object, the robot halts and activates its laser gun to neutralize the threat. Location Tracking: The robot tracks and reports the location of detected threats using location tracking technology. Results: The robot successfully captured and transmitted real-time video of its surroundings, detected intruders and metallic objects, and neutralized threats using the laser gun. Additionally, it accurately tracked and reported the location of detected objects, demonstrating its effectiveness in various surveillance applications. Conclusion: The IoT-based Smart Multi-Application Surveillance Robot significantly enhances battlefield safety and reduces the risk to soldiers by capturing critical information and neutralizing threats before engagement. Its ability to perform multiple functions, including bomb detection and location tracking, underscores its versatility and potential impact on modern security and surveillance practices.